(untitled) (Research, Society and Development, 2022)
The knowledge of water availability in water bodies is of great importance for their management and planning of activities that depend on them. However, great difficulties are encountered during this process, given the lack of data in the vast majority of watersheds. This work presents a technique that has been shown to be efficient in this regard and has been applied by the environmental agency of Mato Grosso do Sul State, but which can also be applied in watersheds of other states: the mapping of minimum flows that, in addition to solving this problem of absence of data, makes the procedure for obtaining hydrological data agile. This research aims to present a methodology for preparing dispersion mapping in minimum flow curves through ordinary kriging, thus helping the flow estimation process, as it serves as a tool for collecting and generating information on reference flow rates by simply inserting the geographic coordinate of the point of interest. Data from 79 fluviometric stations were used and maps were generated for the State of Mato Grosso do Sul. The results obtained were considered satisfactory based on cross validation, where dispersion coefficients around 0.70 were obtained.